Serum osteocalcin and bone mineral density in postmenopausal women - Susanto, Lie T. Merijanti (Universa Medicina, 2011)
Since high bone turnover is associated with decreased bone mass, biochemical markers of bone remodeling, such as serum osteocalcin, may be used to assess osteoporosis and to predict fractures in elderly women, particulary those involving trabecular bone, and use of a combination of bone mineral density (BMD) and biochemical markers may improve fracture prediction. The serum levels of osteocalcin constitute a specific biochemical parameter of bone formation. Compared to imaging techniques, assays for osteocalcin are safe, noninvasive and easily performed. The aim of this study was to determine the relationship of serum osteocalcin and BMD in postmenopausal women. A cross sectional study was performed on 53 postmenopausal women in South Jakarta from February to April 2010. The subjects were assessed for anthropometric characteristics, serum osteocalcin levels and BMD. BMD was measured at the lumbar spine, right femoral neck and at the left distal radius by dual energy X-ray absorptiometry (DXA). Mean serum osteocalcin was 28.99 Â± 10.02 ng/ml. The Pearson correlation test on all subjects indicated a significant inverse correlation between serum osteocalcin and femoral neck BMD (r = - 0.29; p=0.034). By arranging the data into tertiles, a significant association was found in non-obese subjects between mean femoral neck BMD and serum osteocalcin (p=0.036). The Tukey posthoc multiple comparison test showed a significant mean difference in femoral neck BMD between the lowest and the highest tertiles of osteocalcin serum concentrations (p=0.028). Maintenance of body weight is important for maintaining BMD in postmenopausal women.